2009
DOI: 10.1016/j.buildenv.2008.02.012
|View full text |Cite
|
Sign up to set email alerts
|

A numerical investigation into the effect of windvent dampers on operating conditions

Abstract: a b s t r a c tThe United Kingdom has made a commitment to reduce buildings carbon emissions, placing a greater onus on sustainable energy sources. Therefore, an anticipated increase of usage of zero carbon technologies in new and existing building has led to the emergence of passive ventilation devices as an alternative to mechanical ventilation and air conditioning. The windvent is a commercially available passive ventilation device. The device is constructed from sheet metal and works on the principle of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 8 publications
1
26
0
Order By: Relevance
“…In addition to improving human comfort, they have low maintenance cost due to having no moving parts, capturing and supplying clean and fresh air at roof level compared to low level windows [13]. Although it has many advantages, a problem of both modern and traditional multi-channel windcatchers is air-short-circuiting that is reported by different scholars in previous studies [14][15][16][17][18][19] and has a negative impact on the ventilation performance of windcatcher. Air-short-circuiting occurs when the air entering through the supply channel immediately exits through the exhaust without circulating inside the enclosed space (see Fig.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…In addition to improving human comfort, they have low maintenance cost due to having no moving parts, capturing and supplying clean and fresh air at roof level compared to low level windows [13]. Although it has many advantages, a problem of both modern and traditional multi-channel windcatchers is air-short-circuiting that is reported by different scholars in previous studies [14][15][16][17][18][19] and has a negative impact on the ventilation performance of windcatcher. Air-short-circuiting occurs when the air entering through the supply channel immediately exits through the exhaust without circulating inside the enclosed space (see Fig.…”
Section: Introductionmentioning
confidence: 94%
“…The spacing of the occupants was based on reference [19]. model on natural ventilation studies was also found in previous works of [16] and [18] to be reliable and accurate. The governing equations for k-turbulence were not included here but can be found in the ANSYS 14.5 Fluent theory guide [36].…”
Section: Computational Fluid Dynamics (Cfd) Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…The average of difference between experimental data and mentioned model was 11% (lower than the other two models). Therefore, standard k-model was selected for current numerical study which was in agreement with pervious windcatcherstudies in reference of [34] and [35]. …”
Section: Sensitivity Of Turbulence Modelmentioning
confidence: 99%